The Effectiveness of Google Classroom Media on the Students’ Learning Outcomes of Madrasah Ibtidaiyah Teacher Education Department - Fauzan Fauzan; Fatkhul Arifin (UIN Siber Syekh Nurjati Cirebon, 2019)
AbstractThis study aims to determine the effectiveness of the use of google classroom media on students’ learning outcomes at Madrasah Ibtidaiyah Teacher Education Department of UIN Syarif Hidayatullah Jakarta. The research adopts qualitative method, which examines students’ learning outcomes using google classroom media, where researchers apply the media during learning instruction. Data collection techniques used were students’ learning outcomes, in-depth interviews, and documentation. Data analysis using interactive models and testing the validity of data using tests of credibility (internal validity), transferability (external validity), dependability (reliability), and cconformability (objectivity). The results showed that the use of google classroom media was effective in improving the students’ learning outcomes of Madrasah Ibtidaiyah Teacher Education Department of UIN Syarif Hidayatullah Jakarta. Therefore, the use of google classroom media can be used as an alternative media in the learning process.Keywords: google classroom media, e-learning, learning outcomes.AbstrakPenelitian ini bertujuan untuk menentukan efektivitas penggunaan media google clasroom terhadap hasil belajar mahasiswa jurusan Pendidikan Guru Madrasah Ibtidaiyah UIN Syarif Hidayatullah Jakarta. Metode penelitian yang digunakan adalah metode kaulitatif, yakni menelaah hasil belajar mahasiswa yang menggunakan media google classroom, di mana peneliti menerapkan media tersebut pada saat pembelajaran. Teknik pengumpulan data yang digunakan adalah hasil belajar mahasiswa, wawancara mendalam dan dokumentasi. Analisis data menggunakan model interaktif dan pengujian keabsahan data menggunakan uji credibility (validitas internal), transferability (validitas eksternal), dependability (reliabilitas), dan Confirmability (objektivitas). Hasil penelitian menunjukkan bahwa penggunaan media google classroom efektif dalam meningkatkan hasil belajar mahasiswa jurusan Pendidikan Guru Madrasah Ibtidaiyah UIN Syarif Hidayatullah Jakarta. Oleh karena itu, penggunaan media google classroom dapat dijadikan sebagai media alternative dalam proses pembelajaran.Kata kunci: media google classroom, e-learning, hasil belajar.